2018
DOI: 10.1016/j.advwatres.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

A centennial catalogue of hydro-geomorphological events and their atmospheric forcing

Abstract: The DISASTER database records 1969 unique hydro-geomorphologic cases (floods and landslides) that generated human damages in Portugal during a 150 year-period (1865-2015. The main purposes of this work are the following: to present a national disaster events catalogue; to analyse the atmospheric conditions and to discuss the role of rainfall as main driving force of the hydro-geomorphological disaster events. The main Circulation Weather Types (CWTs) and the presence of Atmospheric Rivers (ARs) of each day of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 60 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…To facilitate the interpretation of the resulting daily CWTs, we separate them into the respective pure directional (from north: N, NE, E, SE, S, SW, W, and NW) and cyclonic/anticyclonic (C/A) types, thus resulting in a total of 10 CWTs, using the same method as in Ramos et al (2014). Furthermore, the directional types are grouped according to similar coherent precipitation responses (Ramos et al 2014;Pereira et al 2018). Thus, the following subset of grouped CWTs is considered: 1) cyclonic (C), 2) anticyclonic (A), 3) wet zonal types (NW1W1SW), 4) cold types (N1NE), and 5) warm types (S1SE1E).…”
Section: E Circulation Weather Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate the interpretation of the resulting daily CWTs, we separate them into the respective pure directional (from north: N, NE, E, SE, S, SW, W, and NW) and cyclonic/anticyclonic (C/A) types, thus resulting in a total of 10 CWTs, using the same method as in Ramos et al (2014). Furthermore, the directional types are grouped according to similar coherent precipitation responses (Ramos et al 2014;Pereira et al 2018). Thus, the following subset of grouped CWTs is considered: 1) cyclonic (C), 2) anticyclonic (A), 3) wet zonal types (NW1W1SW), 4) cold types (N1NE), and 5) warm types (S1SE1E).…”
Section: E Circulation Weather Typesmentioning
confidence: 99%
“…Variability in ARs characterized by the IVT has been analyzed in western Europe (e.g., Sodemann and Stohl 2013;Villarini 2015, 2013;Ramos et al 2015), western North America (e.g., Ralph and Dettinger 2011;Brands et al 2017;Hecht and Cordeira 2017;Oakley et al 2018), South Africa (e.g., Blamey et al 2018;Ramos et al 2018), and Chile (Viale et al 2018), among other regions. In fact, important historical flooding events can be attributed to ARs over western Europe (e.g., Lavers et al 2011;Lavers and Villarini 2013;Pereira et al 2018). Likewise, severe water shortages are associated with an anomalous and persistent decrease of IVT toward these western coastal areas (Dettinger 2013;Flint et al 2018;Sousa et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Within extratropical cyclones, concurrent wind and precipitation are likely to occur along with frontal structures (Catto and Pfahl, 2013;Schemm et al, 2016) and their intensity scales with the frontal strength (Schemm et al, 2017;Raveh-Rubin and Catto, 2019). For the Iberian Peninsula (IP), extreme windstorms and extreme precipitation are among the costliest natural hazards (Lorente et al, 2008;Liberato and Trigo, 2014;Pereira et al, 2018). This topic has become of great interest to the general public, stakeholders, and reinsurance companies, which deal with increasing rebuilding costs and due compensations, in the framework of increasing risk under climate change (Aon-Benfield, 2018;Munich, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation and meteorological conditions associated with landslides occurrence in Portugal, especially in the Lisbon region, have been studied in the past (e.g., Zêzere et al, 2005;Zêzere et al, 2015;Pereira et al, 2018). It was shown by Zêzere et al (2005), that the precipitation, North Atlantic Oscillation and landslide occurrence in the Lisbon region were associated 255 through a 3-month moving average computed to both the NAO index and the monthly rainfall anomalies.…”
Section: Association Between Landslides and Clustering Of Rainfallmentioning
confidence: 99%
“…Recent studies also show that over western Iberian Peninsula extreme precipitation is often associated with the landfall of Atmospheric Rivers (Ramos et al, 2014;Trigo et al, 2014;Eiras-Barca et al, 2016 2018) analyzed a centennial catalogue of hydro-geomorphological events (including floods and landslides) and their atmospheric forcing and also concluded that the westerly flow and the cyclonic types are mainly associated with these hydro-geomorphological events. In addition, regarding the 130 events analyzed by Pereira et al (2018), it was shown that around 45% were somehow associated with the passage of an Atmospheric River. For comparison purposes, for the trigger days of the landslides (62 days) analyzed in this paper, we have extracted the circulation weather types from the same database that was used by Pereira et al (2018).…”
mentioning
confidence: 99%